Busy female directors: an exploratory analysis of the impact of quotas and interest groups. Issue 3 (24th January 2021) - Sarabi, Yasaman; Smith, Matthew
Abstract : Purpose: This paper aims to provide an exploratory analysis of male and female directors, comparing the case of UK FTSE 350 boards of directors for 2010–2018, with Norwegian boards from 2002 to 2018, to examine patterns of busy female directors. This paper considers the differences between the effects of interest groups' actions and those of quotas on the emergence of busy female directors. Design/methodology/approach: This paper uses a longitudinal approach, providing an examination of both non-busy directors and busy directors sitting on the boards of UK and Norwegian firms, with a focus on female directors. Drawing on methods from social network analysis, several trends and patterns are mapped for the two corporate systems. The paper tests whether the proportion of busy male directors is significantly different from the proportion of busy female directors in the two institutional settings. Findings: The results show there has been an increase in the proportion of busy female directors, whereas the level of busy male directors is slightly decreasing in the UK from 2010 to 2018. In Norway, following the introduction of gender quotas on corporate boards, there has been an increase in overboarded directors, especially female directors, along with the rise of so-called "golden skirt" directors. However, when compared to the UK case, the proportion of busy male and female directors is higher, suggesting that the emergence of the golden skirts in Norway is not a result of quotas alone. Originality/value: The topic of busy directors has received increased attention in recent years, yet the gender of these directors is often neglected. This paper provides an overview of the characteristics of busy female directors for large UK and Norwegian firms, presenting avenues for future research.